2022
DOI: 10.3390/genes13071176
|View full text |Cite
|
Sign up to set email alerts
|

Overview of Transcriptomic Research on Type 2 Diabetes: Challenges and Perspectives

Abstract: Type 2 diabetes (T2D) is a common chronic disease whose etiology is known to have a strong genetic component. Standard genetic approaches, although allowing for the detection of a number of gene variants associated with the disease as well as differentially expressed genes, cannot fully explain the hereditary factor in T2D. The explosive growth in the genomic sequencing technologies over the last decades provided an exceptional impetus for transcriptomic studies and new approaches to gene expression measuremen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 139 publications
0
12
0
Order By: Relevance
“…It might be crucial to study the genetic and environmental factors associated with T2D in relation to the risk of the development of hyperglycemia in pregnancy. The findings of the transcriptomic studies of T2D using the scRNA-seq approach were reviewed by Tonyan et al [ 10 ]. The application of single-cell sequencing technology has shown the high proliferative capacity of pancreatic progenitor cells and their developmental heterogeneity and dedifferentiation processes in adult T2D patients.…”
Section: The Recent Discoveries In the Scrna-seq Studies Of Human Pre...mentioning
confidence: 99%
See 1 more Smart Citation
“…It might be crucial to study the genetic and environmental factors associated with T2D in relation to the risk of the development of hyperglycemia in pregnancy. The findings of the transcriptomic studies of T2D using the scRNA-seq approach were reviewed by Tonyan et al [ 10 ]. The application of single-cell sequencing technology has shown the high proliferative capacity of pancreatic progenitor cells and their developmental heterogeneity and dedifferentiation processes in adult T2D patients.…”
Section: The Recent Discoveries In the Scrna-seq Studies Of Human Pre...mentioning
confidence: 99%
“…To date, a lot of findings have been accumulated in the analysis of gene expression changes associated with pregnancy abnormalities [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. Despite the aforementioned progress in using transcriptome analysis methods in various pregnancy-associated disorders, the etiologies of these diseases remain unexplored or not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…The transcriptomics studies have strengthened our knowledge of genetic factors associated with the development and associated outcomes of diabetes. Importantly, different groups have utilized the insulin-targeted organs, such as the pancreas, liver, skeletal muscles, adipose tissues, etc., for gene expression studies reflecting the dominance of inflammatory immune responses in the pathogenesis of diabetes (Corbi et al, 2020; Lin et al, 2020; Tonyan et al, 2022); however, LSK transcriptome under long-standing diabetes has not been studied well. In addition to mRNA targets, non-coding RNAs like micro RNAs (miRNA) have been widely explored (He et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, DAG can activate protein kinase C (PKC) in muscle and liver [ 20 ], inhibiting insulin signaling and promoting skeletal muscle and liver insulin resistance, leading to systemic insulin resistance [ 21 ] and a variety of metabolic disorders such as hyperglycemia, hypertension, dyslipidemia, non-alcoholic fatty liver (NAFLD) and T2D [ 22 ]. Several studies revealed differentially expressed genes (DEGs) associated to insulin resistance [ 23 ]. However, the difference in transcriptomic progression and core pathways affected from normal glucose-tolerant obese individuals to T2D obese individuals in WAT is still unclear.…”
Section: Introductionmentioning
confidence: 99%